2001
DOI: 10.1101/gad.903901
|View full text |Cite
|
Sign up to set email alerts
|

Functional antagonism between E2F family members

Abstract: E2F is a heterogenous transcription factor and its role in cell cycle control results from the integrated activities of many different E2F family members. Unlike mammalian cells, that have a large number of E2F-related genes, the Drosophila genome encodes just two E2F genes, de2f1 and de2f2. Here we show that de2f1 and de2f2 provide different elements of E2F regulation and that they have opposing functions during Drosophila development. dE2F1 and dE2F2 both heterodimerize with dDP and bind to the promoters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
217
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(243 citation statements)
references
References 72 publications
23
217
2
1
Order By: Relevance
“…Unexpectedly, reducing the gene dosage of rbf, de2f2, or dDP all substantially suppress the phenotype of de2f1 null mutants (Du, 2000;Frolov et al, 2001), suggesting that the phenotype of de2f1 mutants is at least in part due to the presence of an RBF/dE2F2 repressor complex. Characterization of the de2f1 and de2f2 double mutant or dDP mutant flies revealed slower progression through S phase and a defect in the G2/M transition (Frolov et al, 2001). Combining the de2f2 mutant with a novel allele of dE2F1 (dE2F1 su89 ), which retains the transcription activation function but disrupts interaction with RBF, allowed the characterization of the active repression function of Rb/E2F complexes.…”
Section: Biological Functions Of the Rb And E2f Family Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, reducing the gene dosage of rbf, de2f2, or dDP all substantially suppress the phenotype of de2f1 null mutants (Du, 2000;Frolov et al, 2001), suggesting that the phenotype of de2f1 mutants is at least in part due to the presence of an RBF/dE2F2 repressor complex. Characterization of the de2f1 and de2f2 double mutant or dDP mutant flies revealed slower progression through S phase and a defect in the G2/M transition (Frolov et al, 2001). Combining the de2f2 mutant with a novel allele of dE2F1 (dE2F1 su89 ), which retains the transcription activation function but disrupts interaction with RBF, allowed the characterization of the active repression function of Rb/E2F complexes.…”
Section: Biological Functions Of the Rb And E2f Family Of Proteinsmentioning
confidence: 99%
“…Interestingly, the two Drosophila E2F proteins behave like the first two subgroups of the mammalian E2F proteins: dE2F1 mainly functions as a transcription activator (Du, 2000;Frolov et al, 2001), comparable to the mammalian-activating E2Fs 1-3, while dE2F2 primarily mediates active repression, similar to the mammalian-repressive E2Fs 4 and 5 (Frolov et al, 2001). Furthermore, similar to the mammalian Rb protein that can bind to both the activating and the repressive E2F proteins, RBF can bind to both dE2F1 and dE2F2 proteins in Drosophila (Frolov et al, 2001). In contrast, RBF2 can only bind dE2F2 (Stevaux et al, 2002) analogous to the mammalian p107/p130 proteins that bind preferentially to the repressive E2F proteins (see Figure 3).…”
Section: E2f Transcription Factors In Mammalsmentioning
confidence: 99%
“…Two dE2F genes have been identified in Drosophila, dE2F1 and dE2F2. 23,25,34 dE2F1 (named here dE2F) has been shown to control RNR2 and At 120 h AED (after egg deposition) wing discs were dissociated and analyzed by FACS. en-GAL4; UAS-GFP; UAS-LacZ control disc were compared to en-GAL4; UAS-GFP; UAS-vg discs.…”
Section: Vg and Sd Induce Proliferation Of Hela Cellsmentioning
confidence: 99%
“…It has been shown that the human E2F-6 and Drosophila dE2F2 proteins function as repressors for E2F-regulated genes (17)(18)(19)(20)(21)(22). AtE2F2, one of three Arabidopsis E2F homologs that exhibit an overall similarity to animal E2Fs, has been shown to have no transactivation function due to the lack of an activation domain (37), suggesting that AtE2F2 is structurally and functionally similar to E2F-6 and dE2F2.…”
Section: Fig 6 Subcellular Localization Of Gfp Proteins Fused Withmentioning
confidence: 99%
“…An E2F site-mediated repression is also conferred by the direct binding of a repressor-type E2F such as E2F-6 in mammals and dE2F2 in Drosophila (17)(18)(19)(20)(21). E2F-6, unlike other mammalian E2Fs, lacks a transcriptional activation domain and likely functions as a dominant negative repressor independently of pocket proteins.…”
mentioning
confidence: 99%